The Potential of Sharia Tourism Muara Jambi Temple on Regional Economic Growth - Fradesa, Fiza (JESI (Jurnal Ekonomi Syariah Indonesia), 2022)
Abstract This scientific article aims to discuss The Potential of Sharia Tourism Muara Jambi Temple on Regional Economic Growth. The data collection techniques in this study used qualitative methods through observation, interviews, documentation, and triangulation techniques, as well as data analysis techniques, namely data reduction, data presentation, and conclusion drawing and verification. The results of his research are that Muara Jambi Temple has the potential to become sharia tourism, seen from its development which can have a significant impact on the economy, about 45% of the people around the temple area who depend their lives on this tourist spot. However, when viewed as a whole, this tourist spot has no potential as a sharia tourist place because in its management there are still several policies that do not lead to sharia rules, so improvements and improvements still need to be reviewed so that later this place can be used as sharia tourism, it is predicted around 10-15 years later this temple can be realized as a sharia tourism. The government and related stakeholders are expected to further strengthen the synergy to build Jambi tourism for the better in order to increase regional economic growth. Keywords: Potential, Sharia Tourism, Economic Growth.